2015
DOI: 10.1002/art.39004
|View full text |Cite
|
Sign up to set email alerts
|

The Parasitic Worm Product ES‐62 Targets Myeloid Differentiation Factor 88–Dependent Effector Mechanisms to Suppress Antinuclear Antibody Production and Proteinuria in MRL/lpr Mice

Abstract: ObjectiveThe hygiene hypothesis suggests that parasitic helminths (worms) protect against the development of autoimmune disease via a serendipitous side effect of worm-derived immunomodulators that concomitantly promote parasite survival and limit host pathology. The aim of this study was to investigate whether ES-62, a phosphorylcholine-containing glycoprotein secreted by the filarial nematode Acanthocheilonema viteae, protects against kidney damage in an MRL/lpr mouse model of systemic lupus erythematosus (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 74 publications
2
60
0
Order By: Relevance
“…ES-62 exhibits the ability to modulate Th1-, Th17- and Th22-mediated responses, particularly when these phenotypes are dysregulated during development of pathogenesis in mouse models of rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and asthma2456. For example, in the Collagen-Induced Arthritis (CIA) model of RA where Th1/Th17 responses are pathogenic, ES-62 targets DCs to suppress their priming of such aberrant Th and γδ T cells4.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…ES-62 exhibits the ability to modulate Th1-, Th17- and Th22-mediated responses, particularly when these phenotypes are dysregulated during development of pathogenesis in mouse models of rheumatoid arthritis (RA), systemic lupus erythematosus (SLE) and asthma2456. For example, in the Collagen-Induced Arthritis (CIA) model of RA where Th1/Th17 responses are pathogenic, ES-62 targets DCs to suppress their priming of such aberrant Th and γδ T cells4.…”
Section: Resultsmentioning
confidence: 99%
“…ES-62 is a PC-containing immunomodulatory glycoprotein that exhibits protective effects in models of allergic and autoimmune disease911 by homeostatically resetting the effector: regulatory B cell balance and consequently modulating the IL-23/IL-17/IL-22 inflammatory axis2345630, dysregulation of which has been implicated in the pathogenesis of chronic inflammatory disorders31. Although the precise cellular networks modulated by the worm product appear to differ depending on the inflammatory context, ES-62 likely affords protection by acting to subvert TLR signalling via partial downregulation of MyD88 expression in effector cells of both innate and adaptive immunity346917.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Amongst the best characterised ES products is ES-62, a phosphorylcholine (PC)-containing glycoprotein secreted by the rodent filarial nematode Acanthocheilonema viteae that we have shown to prevent initiation and progression of pathology in mouse models of certain allergic (asthma, contact dermatitis) and autoimmune (RA, SLE) inflammatory diseases 1,2,[38][39][40][41][42][43] . Collectively, our studies have identified a unifying mechanism of action that allows effective protection irrespective of the inflammatory phenotype: thus, by subverting TLR4 signalling to downregulate aberrant MyD88-responses, ES-62 acts to homeostatically reset the regulatory:effector immune cell balance, primarily to restore levels of IL-10 + regulatory B cells (Bregs) and suppress pathological IL-17-driven inflammation 1,2,[38][39][40][41][42][43][44] . In experimental models of RA and human disease, perturbation of the microbiota has been shown to disrupt the balance of pathogenic Th17 cells and the counter-regulatory Bregs and Tregs that act to homeostatically resolve inflammation 20,[24][25][26] .…”
Section: Introductionmentioning
confidence: 99%